Assessment of the Endophytic Fungal Composition of Lactobacillus plantarum and Enterococcus faecalis-Fermented Astragalus membranaceus Using Single-Molecule, Real-Time Sequencing Technology - Zhang, Liheng; Li, Xianghui; Song, Xinghui; Bian, Chuanzhou; Kang, Xiangtao; Zhao, Junqiang; Qiao, Hongxing; Gong, Yanzhang (Frontiers in Veterinary Science, 2022)
Endophytic fungus represents microorganism existing within the healthy plant organs, which can significantly influence metabolic products production in plants, a process with great research value and broad prospects for development. To investigate the effect of fermentation with probiotic cultures on the endophytic fungal diversity and composition of Astragalus membranaceus, we used single-molecular, real-time sequencing (Pacific Biosciences) for18S rRNA sequencing. The results showed that endophytic fungi of Astragalus membranaceus mainly belonged to Aspergillus, Penicillium, Cystofilobasidium, Candida, Guehomyces and Wallemia. Furthermore, the endophytic fungal diversity and abundance of Astragalus membranaceus were more variable after fermentation with Enterococcus faecium and/or Lactobacillus plantarum. Our data lays a solid and comprehensive foundation for further exploration of endophytic fungi from A. membranaceus as potential sources of functional compounds.